Managemen Keuangan di SMP Muhammadiyah Al-Manar Galur - Tajkiatu Zahra; Ulil Jannah; Farid Setiawan (Global Leadership Organizational Research in Management, 2024)
The aim of this research is to describe the implementation of educational financial management in the aspects of planning, implementation, evaluation and accountability of educational finances at Al-Manar Galur Muhammadiyah Middle School. At Muhammadiyah AL-Manar Galur Middle School, financial management is an urgent matter because education faces obstacles in managing limited funds and budgets. Al-Manar Galur Muhammadiyah Middle School often faces limited financial resources, but has an obligation to improve the facilities and quality of education. Setting the budget in detail and systematically Al-Manar Galur Middle School needs to make arrangements so that every expenditure can be properly accounted for. Good financial management at AL-Manar Galur Middle School can help the institution provide student infrastructure and change education for the better. Managing finances effectively can contribute to increasing the efficiency of using funds, controlling expenses and transparent financial reporting.